Regulation of desiccation tolerance in Xerophyta seedlings and leaves - Lyall, Rafe (Department of Molecular and Cell Biology, 2017)
A small, diverse group of angiosperms known as resurrection plants display vegetative desiccation tolerance and can survive loss of up to 95% of cellular water, a feat only seen in the seeds and pollen of other angiosperms. Xerophyta humilis is a resurrection plant native to Southern Africa that has been the target of previous transcriptomic and proteomic studies into the mechanisms of plant desiccation tolerance. The aim of this study was to investigate the hypothesis that vegetative desiccation tolerance is derived from the networks that control desiccation tolerance in seeds and germinating seedlings in angiosperms, particularly the epigenetically silenced seed maturation genes. Germinating seedlings of X. humilis and the related resurrection plant X. viscosa were found to be VDT from the earliest stages of germination, and exhibited the characteristic vegetative trait of poikilochlorophylly as seen in mature leaves. The X. humilis desiccation transcriptome comprising 76,768 distinct gene clusters was successfully assembled from sequencing samples at five relative water contents (100%, 80%, 60%, 40% and 5%) to identify the networks activated in response to water loss. Desiccation was associated with successive waves of transcription factor induction, as well as widespread down-regulation of histone modification enzymes. Many seed-specific genes, such as late embryogenesis abundant (LEA) proteins, seed storage proteins and oleosins, were induced in vegetative tissue. LEA transcripts in particular were highly up-regulated during desiccation, and the large number of distinct LEA transcripts (over 150) suggests possible LEA gene expansion in Xerophyta compared to desiccation-sensitive plants. Components of the PYL/SnRK2/ABF ABA-signalling pathway were also induced, although the ABF transcription factors activated in response to desiccation were most similar to those induced by drought in A. thaliana rather than seed maturation. Of the canonical seed master regulators (such as the LEC1/ABI3/FUS3/LEC2 network and ABI5) only three ABI3 transcripts were expressed, all of which encoded proteins lacking the seed motif-binding B3-domain. The results of this study suggest that vegetative desiccation tolerance in X. humilis is not associated with re-activation of seed master regulators in vegetative tissue, but may instead involve activation of seed genes by vegetative drought response regulators.